Review of major shale-dominated detachment and thrust characteristics in the diagenetic zone: Part I, meso- and macro-scopic scale - C. K. Morley (2018)
© 2017 Elsevier B.V. There is considerable variability in the thickness, structure, and macroscopic deformation style within shale-prone major thrust zones, which also impacts the structural style in the overlying, and sometimes the underlying section. The properties and percentages of clay minerals, and percentages of organic material, quartz and calcite affect fault zone weakness and behaviour. The distribution of competent units within a shale-prone zone can also significantly affect fault zone architecture, even over short strike distance of 10s to 100s of metres. Other influences include high pore fluid pressures, and associated veins. Deformation of the fault zone may disrupt the original principal displacement zones and force them to relocate, including switching lithologies. Calcite veins can become concentrated locally in the fault zone, and become a focus of fault zone weakness. We still need many more descriptions of shale-prone fault zones to understand the potential variations in thrust sheet structural style caused by differences in shale detachment characteristics. The variations in structural style in the hanging walls of shale detachments are broad and range between the sledge-runner style in many Appalachian examples, and the extensive, closely spaced imbricate style of the Osen-Røa detachment, Southern Norway. Such contrasts are related to several factors including: thrust sheet mechanical stratigraphy, thickness of the overburden, lateral continuity of the detachment, detachment mechanical properties (composition, pore fluid pressures), presence/absence of higher level detachments and strain rate. In many structural locations, and at many scales, shale prone sequences will pile-up to produce over thickened masses. Cleavage duplexes, S-C fabrics, duplexes, imbricates, pseudo-duplexes and vein formation can all contribute to the thickening at nested scales. A mixture of brittle and solution/diffusion processes overall cause the affected unit to exhibit flow-like characteristics. While the broad principles are now well-established, considerable work remains to be done understanding the full range of structural geometries associated with shale detachments, what factors regarding the nature of the detachments affect overlying structural styles, rates of deformation, and the controls on deformation mechanisms within the thrust zones.